Transition from microcellular to nanocellular PLA foams by controlling viscosity, branching and crystallization. (June 2017) - Tiwary, Praphulla; Park, Chul B.; Kontopoulou, Marianna
Graphical abstract: Highlights: PLA foams are produced by batch foaming using supercritical nitrogen. Reducing the foaming temperature results in smaller cell sizes. Introduction of branching results in smaller cell sizes and larger expansion ratio. Branched and nucleated PLA is produced by reactive extrusion. This formulation results in sub-micron sized cells and very high cell densities. Abstract: This study investigates the influence of material properties and foaming temperature on the cellular structure of foams produced by batch foaming of linear, branched and nucleated polylactide (PLA), using supercritical nitrogen. Higher viscosities, corresponding to low foaming temperatures, resulted in smaller cell sizes within the investigated foaming temperature range of 140–180 °C, whereas higher foaming temperatures favoured larger volume expansion ratio ( VER ). In the presence of branching the PLAs exhibited strain hardening, which served to stabilize the foams and resulted in a finer cellular structure and improved VER s. Formulations containing boron nitride (BN) nucleating agent could not foam at the lowest temperature of 140 °C, because of crystallization taking place at this temperature. A combination of branching and nucleation achieved by reactive modification of PLA using peroxide and coagent crosslinking agents yielded the best results. The cell densities of foams made out of this formulation were significantly higher compared to the rest of the formulations, of the order of 10 11  cells/cm 3 . Very fine, sub-micron sized foams were obtained when this material was foamed at 140 °C, which is close to its exothermic crystallization temperature. This work provides guidelines of the ranges of material property values that are more conducive to achieve micro- and sub-micron sized foams.